Genetic Variability Studies in BC2F2 Population Derived from Samba Mahsuri * 2/ O.rufipogon of Rice - C. GIREESH, M. SRIDHAR, M. SUJATHA, R.M. SUNDARAM DIVYA BALAKRISHNAN, D. SRINIVASA CHARY (The Journal of Research, PJTSAU, 2020)
Rice crop is endowed with a rich geneticvariability. However, intensive modern breeding effortsfurther narrowed the rice gene pool because of selectionpressure in favour of favourable alleles and hence themodern rice cultivars have narrow genetic base for mostof the agronomically important traits including yield.